Neuroscience Attitudes, Exposure, and Knowledge among Counselors - Eric T. Beeson; So Rin Kim; Carlos P. Zalaquett; Fiona D. Fonseca (Teaching and Supervision in Counseling, 2019)
The purpose of this study was to explore the neuroscience attitudes, exposure, myths, and knowledge among counselors at various stages of their careers. Descriptive statistics were used to highlight the current state of neuroscience attitudes, exposure, myths, and knowledge among a sample of counselors (N = 416). The results showed that participants had positive attitudes towards neuroscience, were exposed to neuroscience information through various methods, believed neuroscience should be integrated in over half of the counselor education curriculum, had high levels of neuroscience knowledge (85%), and had average levels of neuromyths endorsed (56%). The results provide insights that can guide the infusion of neuroscience into the counselor education curriculum.
Keywords: neuroscience; neurocounseling; neuromyths